2017
DOI: 10.1038/s41598-017-13476-z
|View full text |Cite
|
Sign up to set email alerts
|

Host heterozygosity and genotype rarity affect viral dynamics in an avian subspecies complex

Abstract: Genetic diversity at community, population and individual levels is thought to influence the spread of infectious disease. At the individual level, inbreeding and heterozygosity are associated with increased risk of infection and disease severity. Host genotype rarity may also reduce infection risk if pathogens are co-adapted to common or local hosts, but to date, no studies have investigated the relative importance of genotype rarity and heterozygosity for infection in a wild, sexually reproducing vertebrate.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 59 publications
(113 reference statements)
3
24
0
Order By: Relevance
“…In the current study, we found that low multilocus heterozygosity-which previous work has shown to correlate with inbreeding in crows (Townsend et al 2009a(Townsend et al , 2010b)-was associated with two vector-borne infectious diseases: an emerging epidemic pathogen (WNV) and an endemic, common one (Plasmodium spp). Overall, our results support the widely held hypothesis that inbred individuals may be more susceptible to certain infections than outbred individuals (Altizer et al 2003, Spielman et al 2004, Eastwood et al 2017, and provides empirical data-rare in wild, free-living populations-on how this susceptibility varies among specific pathogens. We found no associations between heterozygosity and infection by Campylobacter jejuni, a common and widespread bacterial pathogen with a fecal-oral transmission route.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In the current study, we found that low multilocus heterozygosity-which previous work has shown to correlate with inbreeding in crows (Townsend et al 2009a(Townsend et al , 2010b)-was associated with two vector-borne infectious diseases: an emerging epidemic pathogen (WNV) and an endemic, common one (Plasmodium spp). Overall, our results support the widely held hypothesis that inbred individuals may be more susceptible to certain infections than outbred individuals (Altizer et al 2003, Spielman et al 2004, Eastwood et al 2017, and provides empirical data-rare in wild, free-living populations-on how this susceptibility varies among specific pathogens. We found no associations between heterozygosity and infection by Campylobacter jejuni, a common and widespread bacterial pathogen with a fecal-oral transmission route.…”
Section: Discussionsupporting
confidence: 83%
“…We found no associations between heterozygosity and infection by Campylobacter jejuni, a common and widespread bacterial pathogen with a fecal-oral transmission route. Overall, our results support the widely held hypothesis that inbred individuals may be more susceptible to certain infections than outbred individuals (Altizer et al 2003, Spielman et al 2004, Eastwood et al 2017, and provides empirical data-rare in wild, free-living populations-on how this susceptibility varies among specific pathogens.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Relations between genomic heterozygosity and plant fitness have been explored in several species, and, when studied at the individual level, these relations serve as a measure of individual genetic diversity (Arct et al, 2017;Eastwood et al, 2017). Our analysis revealed modest negative correlations between heterozygosity and RDM and RV under N stress plus A. brasilense treatment.…”
Section: Individual Heterozygosity and N Status In The Plant Can Regumentioning
confidence: 74%
“…Hence, the competition between A. brasilense and a wide range of other microorganisms that have little or no effect on the plant could have resulted in a lower benefit due to inoculation. In addition, regarding host-pathogen systems, the lower individual genetic diversity can increase the susceptibility to infection (Govindaraj et al, 2015;Eastwood et al, 2017). Similarly, this could happen with A. brasilense, where the allelic diversity among specific loci associated with plant immunity would actively control the extent of colonization by the bacteria and, consequently, the degree of beneficial results.…”
Section: Individual Heterozygosity and N Status In The Plant Can Regumentioning
confidence: 99%